2018
DOI: 10.1088/1361-6641/aacba2
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and phononic properties of PtSe2: from monolayer to bulk

Abstract: The layer dependent structural, electronic and vibrational properties of the 1T phase of two dimensional (2D) platinum diselenide are investigated by means of state-of-the-art firstprinciples calculations. The main findings of the study are: (i) monolayer platinum diselenide has a dynamically stable 2D octahedral structure with 1.66 eV indirect band gap, (ii) the semiconducting nature of 1T-PtSe 2 monolayers remains unaffected even at high biaxial strains, (iii) top-to-top (AA) arrangement is found to be energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 50 publications
18
72
0
1
Order By: Relevance
“…5d. The extracted thickness\intensity ratio is well consistent with the enhanced van der Waals interactions between the layers in thicker 2D materials [68,78,80]. Besides the distinct E g and A 1g modes, Raman peaks ascribed to less prominent LO mode, which attributed to a combination of the in-plane E u and out-of-plane A 2u vibrations, are also observed [43,55].…”
Section: Vibration Spectroscopic Modessupporting
confidence: 76%
“…5d. The extracted thickness\intensity ratio is well consistent with the enhanced van der Waals interactions between the layers in thicker 2D materials [68,78,80]. Besides the distinct E g and A 1g modes, Raman peaks ascribed to less prominent LO mode, which attributed to a combination of the in-plane E u and out-of-plane A 2u vibrations, are also observed [43,55].…”
Section: Vibration Spectroscopic Modessupporting
confidence: 76%
“…Calibration of Green's function with screened Coulomb interaction (GW) is utilized to predict the quantitative values of the bandgap energy. The bandgap opening in few-layer PtSe 2 , reported in other works, 7,8,14,[19][20][21][22][23] is shown to depend strongly on the simulation framework, with a progressive increase in the PtSe 2 energy gap when considering density function theory (DFT), to DFT with the addition of vdW interactions, and finally to DFT with vdW interactions and screened Coulomb interaction. The Bohr radius provides an estimation of when the quantum effects modify the band structure.…”
Section: Introductionmentioning
confidence: 64%
“…The change also occurs in 3L where both the VBM and CBM, respectively, are located in-between M and Γ points. 29 The difference between PtS 2 and PtSe 2 is that the VBM of PtSe 2 goes back to the Γ point at monolayer, as opposed to monolayer PtS 2 in which the VBM is still in-between M and Γ points. With this, we observe that there is minimal to no shift of indirect-to-direct band gap as the thickness decrease for the PtSe 2 structure.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that these specific TMDs have unique electronic properties that are suitable for a wide range of optoelectronic device applications 21,22 and hydrogen-evolution reaction. 24 Moreover, theoretical studies [27][28][29][30][31][32][33][34][35] regarding noble TMDs, specifically on PtX 2 and PdX 2 , have been conducted. However, they are mostly either focused on the properties of fewlayer structures, or on other specific TMD materials.…”
Section: Introductionmentioning
confidence: 99%